2009
DOI: 10.1002/sim.3517
|View full text |Cite
|
Sign up to set email alerts
|

How to evaluate the calibration of a disease risk prediction tool

Abstract: To evaluate the calibration of a disease risk prediction tool, the quantity E/O, i.e. the ratio of the expected to the observed number of events, is usually computed. However, because of censoring, or more precisely because of individuals who drop out before the termination of the study, this quantity is generally unavailable for the complete population study and an alternative estimate has to be computed. In this paper, we present and compare four methods to do this. We show that two of the most commonly used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 31 publications
0
37
0
Order By: Relevance
“…Lastly, we would like to stress the importance of proper methodology for adjusting the risk scores to correspond to a follow-up time that is less than 10 years. In several publications, the follow-up times have been modified independently of the actual event status, leading to biases in the SIR estimation 28. Here, the aforementioned bias was accounted for (details in the online supplement).…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, we would like to stress the importance of proper methodology for adjusting the risk scores to correspond to a follow-up time that is less than 10 years. In several publications, the follow-up times have been modified independently of the actual event status, leading to biases in the SIR estimation 28. Here, the aforementioned bias was accounted for (details in the online supplement).…”
Section: Discussionmentioning
confidence: 99%
“…The expected numbers of events and nonevents were used in the estimation of NRI to account for censored data and calculated by multiplying the total number of people by the Kaplan-Meier rates at the end of follow-up. This approach was found optimal for assessing calibration of survival models (21 ). We estimated the bias-corrected CIs for NRI by bootstrap resampling (1000 replicates).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…To our knowledge, the Hosmer-Lemeshow statistic has never been extended to survival outcomes. However, as mentioned in Viallon et al (2009), this statistic can be computed with observed counts replaced by their estimates based on Kaplan-Meier estimator. Some more study would be needed to assess the asymptotical distribution of the resulting statistic under the null hypothesis in order to derive a proper statistical test.…”
Section: Assessing the Accuracy Of Aucmentioning
confidence: 99%
“…Most of the existing criteria were originally defined for diagnostic tests and rely on the observation of a binary outcome representing, for instance, disease status. Extending these criteria to survival outcomes is generally not straightforward, especially because of the presence of censored data (see, e.g., Viallon et al (2009) for the calibration of risk prediction tools). In the present work we will focus on methods that assess discrimination of prognostic tools.…”
Section: Introductionmentioning
confidence: 99%